1999
DOI: 10.1038/sj.bmt.1701632
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy with interleukin-2 and α-interferon after IL-2-activated hematopoietic stem cell transplantation for breast cancer

Abstract: Summary:We previously demonstrated findings suggestive of autologous GVHD in patients receiving IL-2-activated peripheral blood stem cells (PBSC) with IL-2 after transplantation. A pilot study was designed to test tolerability, feasibility and frequency of autologous GVHD and engraftment using IL-2 and ␣-IFN posttransplantation. After cyclophosphamide (6 g/m 2 ) and carboplatin (1800 mg/m 2 ), patients with high-risk stage II or III breast cancer received chemotherapy and rhG-CSF mobilized autologous PBSC that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 13 publications
(20 reference statements)
2
14
0
Order By: Relevance
“…Following initial reports of the feasibility and immunologic potential of post-transplant IL-2 immunotherapy, 5-7 many investigators explored IL-2 and/or IL-2-activated effectors for a variety of malignancies with encouraging but inconclusive results. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] We previously reported the results of a phase I trial of post-autologous transplant s.c. IL-2 (Amgen Inc., Thousand Oaks, CA, USA). 4 In all, 12 patients (six lymphoma, six breast cancer) were enrolled on a dose-escalation study of s.c. IL-2 given for 84 days; the best-tolerated dose was 0.25 Â 10 6 U/m 2 /day.…”
Section: Discussionmentioning
confidence: 99%
“…Following initial reports of the feasibility and immunologic potential of post-transplant IL-2 immunotherapy, 5-7 many investigators explored IL-2 and/or IL-2-activated effectors for a variety of malignancies with encouraging but inconclusive results. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] We previously reported the results of a phase I trial of post-autologous transplant s.c. IL-2 (Amgen Inc., Thousand Oaks, CA, USA). 4 In all, 12 patients (six lymphoma, six breast cancer) were enrolled on a dose-escalation study of s.c. IL-2 given for 84 days; the best-tolerated dose was 0.25 Â 10 6 U/m 2 /day.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are similar to those described by Laughlin et al, 26 who reported no relevant modifications of marrow regeneration using continous intravenous infusion of similar doses of IL-2 (40 000 Cetus units m 2 /day equivalent to 240 000 IU m 2 /day) early after BMT. Similarly, Meehan et al 27 observed no modification of engraftment time using higher IL-2 dosages (600 000 IU m 2 /day) subcutaneously. Our present study extends these findings to patients receiving concomitant IL-2/G-CSF/EPO.…”
Section: Discussionmentioning
confidence: 99%
“…Two clinical studies in women with poor risk breast cancer demonstrated the cytotoxic activity of mobilised PBSC. [7][8][9] The prognosis of stage 4 neuroblastoma has improved significantly with high-dose chemotherapy combined or not with TBI and ASCT as consolidation therapy 1,2 but remains poor. The respective role of autograft contamination by tumour cells and of persistent minimal residual disease is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…6 The early administration of low-dose IL-2 after transplantation of IL-2-activated PBSC was then demonstrated to be feasible in women with poor risk breast cancer. [7][8][9] In the light of these preliminary results we felt that children with solid tumours could benefit from HDC combined with immune modulation. The occurrence of spontaneous regressions, 10 intratumour lymphocyte infiltrates with T cell clonal expansion, 11 and the potential efficacy of immunotherapy 12 all argue in favour of a possible role of the immune system in the fight against neuroblastoma (NB), the most common paediatric tumour.…”
mentioning
confidence: 99%